Dependence of mechanical properties of mitral valve annuloplasty rings on annealing modes - K. Yu. Klyshnikov; T. V. Glushkova; N. A. Shcheglova; A. V. Kostelcev; E. A. Ovcharenko (Вестник трансплантологии и искусственных органов, 2020)
Objective: to investigate dependence of the mechanical properties of mitral annuloplasty rings on heat annealing modes. Materials and methods. The study evaluates the nature of change in stress–strain curves under uniaxial compression of experimental samples processed at varying annealing temperature, duration and pressure. Results. It was noted that higher exposure, temperature, and lower pressure led to increased structural rigidity and strength for small strains. Moreover, the extent of influence of annealing temperature and duration was comparable. A 40% (500–700 °C) change in temperature altered the mechanical properties of the ring – 20% increase in strength. A similar change in heat treatment time (4.5–6.5 min) resulted in a 27% increase in the force required for a 15% compression. Conclusion. The experimental dependences presented in the work allow recommending main parameters for heat treatment mode: temperature range 600–700 °C, 10.5 minutes exposure time, and 0.1–0.5 atm air pressure in the furnace chamber.